PENGARUH MODEL DISCOVERY LEARNING DENGAN MEDIA ASSEMBLR EDU TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR - Khaerani Nurfaoziah; Afridha Laily Alindra; Primanita Sholihah Rosmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of the Discovery Learning model assisted by the Assemblr Edu media on the science literacy skills of fifth-grade elementary school students. The background of this research is based on the low level of students’ science literacy and the lack of variety and innovation in instructional media used by teachers. This research employs a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects were students from class VA as the experimental group and class VB as the control group at SDN Cikalongsari I, Karawang Regency, with 22 students in each class. The experimental class received instruction using the Discovery Learning model assisted by Assemblr Edu media, while the control class was taught using the Direct Instruction model. The instrument used was an essay test designed to measure students' science literacy skills based on three indicators: explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting data and scientific evidence. The data analysis results showed that the influence of the Discovery Learning model assisted by Assemblr Edu on students’ science literacy skills reached 51%, and the N-Gain score of the experimental class was 0.76 or 76%, which falls into the high interpretation category. In comparison, the control class using the Direct Instruction model scored 0.68 or 68%, categorized as moderate. These findings indicate a significant improvement in science literacy skills in the experimental class compared to the control class. Therefore, the use of the Discovery Learning model supported by Assemblr Edu media is proven to be effective in enhancing elementary school students’ science literacy skills.